Writing and Printing Papers from Elephant Grass (Themeda cymbaria Hack.) - Bhat, R. V.; Jaspal, Narendra S. (Indian Forester, 1959)
Pilot plant scale experiments on the production of writing and printing papers from elephant grass are described. Pulps were prepared by soda and sulphate processes. Writing and printing papers were made from IOO per cent elephant grass pulp. Four specimens of papers are appended here.